Bismarck and the German Empire, 1871-1918 - Abrams, Lynn (Lancaster pamphlets., 2006)
Bismarck's German Empire has been seen as a paradox, combining an advanced industrial economy and diverse social structure with an authoritarian political system. The author examines the political, economic and social structures of the Empire and the techniques employed by Bismarck to consolidate the regime.